Bipolar electrode and all-solid-state battery
By employing a bipolar electrode structure in an all-solid-state lithium battery, utilizing a porous support framework of lithium-carbon composite material and movable carbon material, the contact between the negative electrode and the solid electrolyte is improved, the interface contact problem is solved, and the battery performance is enhanced.
Patent Information
- Application Number
- CN202410643925.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-22
- Publication Date
- 2025-11-25
AI Technical Summary
Solid-state lithium batteries face obstacles in interface contact, affecting their practical applications, especially the physical contact between the negative electrode and the solid electrolyte and electrochemical side reactions.
The device employs a bipolar electrode structure, in which the negative electrode active material layer contains a lithium-carbon composite material. The anchored carbon material forms a porous support framework, while the non-anchored carbon material is movable, forming a carbon adaptation layer. This improves the physical contact between the negative electrode and the solid electrolyte and prevents electrochemical side reactions.
It improves the physical contact between the negative electrode and the solid electrolyte, stabilizes the interfacial contact, reduces electrochemical side reactions, and enhances the power and cycle life of the all-solid-state battery.
Smart Images

Figure CN121011631A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of lithium batteries, and particularly relates to a novel bipolar electrode and a full-solid-state battery. BACKGROUND
[0002] A full-solid-state lithium battery refers to a lithium battery without any liquid component in the battery and providing charge flow through solid-state conduction of an electrolyte. Compared with a conventional liquid lithium battery, the full-solid-state lithium battery has the advantages of high safety and high capacity density. However, the practical application process of the full-solid-state lithium battery is hindered by some key problems (for example, interface contact problems). For the full-solid-state lithium battery, how to control the interface properties between materials is also a very important topic. SUMMARY
[0003] The present application provides a bipolar electrode having a lithium-carbon composite material layer, in a discharged state, a carbon adaptive layer is formed on the surface of the lithium-carbon composite material outside the electrode, wherein there is a movable carbon material that can move under an external force; the movable carbon material can improve the physical contact between the negative electrode and the solid-state electrolyte, and prevent the electrochemical side reaction between the negative electrode and the solid-state electrolyte without introducing other material layers.
[0004] To achieve the above object, according to one aspect of the present application, a bipolar electrode is provided, the bipolar electrode includes a current collector and a positive electrode active material layer and a negative electrode active material layer located on both sides of the current collector, respectively, the negative electrode active material layer contains a lithium-carbon composite material, the lithium-carbon composite material contains metal nanowires, anchoring carbon material, non-anchoring carbon material, and metal lithium and / or lithium alloy, wherein the anchoring carbon material is a linear carbon material with through holes, the pore size is in the range of 1-100 nm (preferably 2-50 nm), the linear carbon material is wound on the metal nanowires and interwoven to form a porous support skeleton; the non-anchoring carbon material is at least one material selected from carbon black, graphite, mesocarbon microbeads and graphene; the non-anchoring carbon material and the metal lithium and / or lithium alloy are distributed in the pores of the porous support skeleton and on the surface.
[0005] In some embodiments, the metal nanowires include at least one of silver nanowires, copper nanowires, tin nanowires, and magnesium nanowires.
[0006] In some embodiments, the linear carbon material with through holes includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and ordered mesoporous carbons (OMCs, pore size between 2-50 nm).
[0007] In some embodiments, the lithium alloy includes one or more of Li-Au, Li-Mg, Li-Sn, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, and Li-Te, the mass percentage of the alloying element being in the range of 1% to 60%.
[0008] In some embodiments, the mass percentages of the metal nanowire, the anchoring carbon material, the non-anchoring carbon material, and the metal lithium and / or lithium alloy, each, are (1-15):(1-60):(1-60):(35-65), based on 100 mass% of the lithium-carbon composite material.
[0009] In some embodiments, in the case where the lithium-carbon composite material contains both the metal lithium and the lithium alloy, the mass ratio of the metal lithium to the lithium alloy is (55-95):(5-45).
[0010] In some embodiments, the positive electrode active material layer contains an oxide active material or a sulfur positive electrode active material.
[0011] In some embodiments, the oxide active material includes a rock-salt layered active material, a spinel active material, or an olivine active material.
[0012] In some embodiments, the sulfur positive electrode active material includes sulfur (S) or lithium sulfide (Li2S).
[0013] In some embodiments, the rock-salt layered active material includes LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2;
[0014] The spinel active material includes LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4, Li4Ti5O 12 ;
[0015] The olivine active material includes LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4.
[0016] In some embodiments, the positive electrode active material layer contains a high-nickel type ternary positive electrode material having a nickel-cobalt-manganese ratio of 3:1:1 to 8:1:1.
[0017] According to another aspect of the present invention, an all-solid-state battery is provided, the all-solid-state battery comprising a bipolar electrode according to any one of claims 1 to 7.
[0018] In some embodiments, during battery discharge, the negative electrode active material layer forms a carbon adaptation layer on its surface facing the solid electrolyte. The carbon adaptation layer has a thickness ranging from 1 micrometer to 15 micrometers and includes a porous support framework and non-anchored carbon material that can move within the carbon adaptation layer.
[0019] In some embodiments, the carbon adaptation layer also contains alloying elements.
[0020] In some embodiments, the carbon adaptation layer comprises anchored carbon material, movable carbon material, and alloying elements, but does not contain lithium.
[0021] In summary, the present invention has at least one of the following advantages:
[0022] 1. The negative electrode active material layer of the bipolar electrode contains a lithium-carbon composite material, which includes anchored carbon material and non-anchored carbon material. When the lithium battery using this bipolar electrode is discharged, the non-anchored carbon material can move in the surface layer (carbon adaptation layer) of the negative electrode active material layer, thereby greatly improving the physical contact between the negative electrode and other interfaces, especially the physical contact between the negative electrode and the solid electrolyte.
[0023] 2. The carbon adaptation layer formed in the discharge state includes anchored carbon material and movable carbon material. The anchored carbon material maintains the physical contact between the negative electrode and other interfaces and realizes the through-hole transport of lithium ions. The movable carbon material can move in the direction parallel to the negative electrode under external force, so that the force on the negative electrode and other contact surfaces is more uniform and consistent. It can also move in the direction perpendicular to the negative electrode as the deposition surface of metallic lithium in the negative electrode changes.
[0024] 3. The presence of the carbon material adaptation layer greatly improves the physical contact between the negative electrode and the solid electrolyte, and the stable carbon adaptation layer can also avoid electrochemical side reactions between metallic lithium and the solid electrolyte, which is beneficial for the preparation of high-power, long-cycle all-solid-state batteries. Attached Figure Description
[0025] Figure 1 This is a schematic diagram of the lithium-carbon composite material of the present invention;
[0026] Figure 2 This is a schematic diagram of the bipolar electrode of the present invention;
[0027] Figure 3 Here is a scanning electron microscope image of the ablation product in Example 1;
[0028] Figure 4 The image shows a surface electron microscope (SEM) image of the lithium-carbon composite foil prepared in Example 1.
[0029] Figure 5 This is an electron microscope image of the lithium-carbon composite material prepared in Example 1 in a lithium-free state;
[0030] Figure 6 The image shows a surface electron microscope (SEM) image of the lithium-carbon composite foil prepared in Example 2.
[0031] Figure 7 The graph shows the cycle performance test results of the all-solid-state battery. Detailed Implementation
[0032] The lithium-carbon composite material and its applications of the present invention are described in detail below using the accompanying drawings. The following examples are provided only to better understand the principles of the invention and are not intended to limit the scope of protection of the invention. Any equivalent changes or substitutions made by those skilled in the art after reading this specification should be covered within the scope of the claims of this application.
[0033] A schematic diagram of the lithium-carbon composite material of the present invention is shown below. Figure 1 As shown, the lithium-carbon composite material comprises anchored carbon material wound around metal nanowires and interwoven to form a porous support framework, and non-anchored carbon material and lithium and / or lithium alloy distributed in the pores and on the surface of the porous support framework.
[0034] The aforementioned lithium-carbon composite material can be used as the negative electrode active material for lithium batteries. The anchored carbon material is a linear carbon material with through-pores (pore size 1-100 nm). This linear carbon material is wound around metal nanowires and interwoven to form a porous framework structure, serving as the fixing and supporting backbone, and also playing a role in conducting electrons and lithium ions. The non-anchored carbon material is a particulate or sheet-like conductive carbon material, distributed in the pores and on the surface of the porous framework structure. The diameter of the particulate non-anchored carbon material can be 5 nm-50 nm, with carbon black as a representative carbon material; the sheet-like carbon material can have a sheet thickness of 0.5 nm-25 nm and a sheet length ranging from 1 μm to 5 μm. During the discharge process of a lithium battery, as lithium is removed from the negative electrode active material layer, a carbon adaptation layer is formed near the surface of the negative electrode active material layer. The non-anchored carbon material in this layer becomes a movable carbon material. Under the action of external force, it can move in the direction parallel to the negative electrode, making the force on the negative electrode and other contact surfaces more uniform and consistent. It can also move in the direction perpendicular to the negative electrode, as the deposition surface of metallic lithium in the negative electrode changes.
[0035] The lithium-carbon composite material of the present invention can be prepared by the following method, the method comprising the following steps:
[0036] (1) Using a ball milling device, wet ball mill a mixture of non-anchored carbon material, anchored carbon material and alkali metal salt, dry the resulting slurry (preferably freeze-dry) and ablate it in a nitrogen atmosphere;
[0037] (2) The ablated material is mixed evenly with metal nanowires, lithium metal and / or lithium alloy, heated to melt and then extruded to obtain lithium-carbon composite material.
[0038] The alkali metal salt in step (1) can be an alkali metal halide or hydroxide, such as potassium chloride, sodium chloride, sodium hydroxide, etc.
[0039] In step (1), the mass percentages of anchored carbon material, non-anchored carbon material, and alkali metal salt can be in the range of (25-45): (25-45): (10-50).
[0040] Wet ball milling can be carried out in the presence of water or a mixture of water and alcohol.
[0041] In step (1), the ablation temperature can be 600℃-1200℃, preferably 700℃-1000℃; the time can be 0.5 hours-4 hours.
[0042] Figure 2 This is a schematic diagram of the bipolar electrode of the present invention. As shown in the left figure, the bipolar electrode of the present invention has a positive active material layer, a current collector and a lithium-carbon composite material layer in sequence in the thickness direction. As shown in the right figure, a carbon adaptation layer is formed on the surface of the lithium-carbon composite material on the outside of the electrode in the discharge state.
[0043] The bipolar electrode of the present invention can be prepared by a method comprising the following steps:
[0044] 1. Pre-treat the surface of the current collector, including roughening, applying a metal coating or plating, or applying conductive adhesive;
[0045] 2. Apply the positive electrode slurry to one side of the current collector in step 1;
[0046] 3. Roll the lithium-carbon composite material to the other side of the current collector, trim the edges, and obtain a bipolar electrode.
[0047] The bipolar electrode of the present invention can be used in lithium batteries, including liquid batteries, semi-solid batteries, and all-solid batteries, preferably all-solid batteries. In all-solid batteries, the presence of a carbon adaptation layer (mobile carbon material as an interface modulator) during discharge greatly improves the physical contact between the negative electrode and the solid electrolyte.
[0048] The following is a detailed description of each part of the present invention.
[0049] 1. Positive electrode active material layer
[0050] The positive electrode active material layer contains positive electrode active material. It may also optionally contain conductive additives, binders, and other additives. The content of each component in the positive electrode active material layer, such as the positive electrode active material, conductive additives, and binders, is appropriately determined based on the battery design performance. For example, based on the total mass of the positive electrode active material layer as 100% by mass, the content of the positive electrode active material can be 30% or more by mass, 55% or more by mass, or 60% or more by mass, and can be less than 100% by mass or less than 90% by mass. The thickness of the positive electrode active material layer can, for example, be 1 μm or more, 10 μm or more, or 20 μm or more. Alternatively, the thickness of the positive electrode active material layer can be less than 1 mm, less than 500 μm, or less than 100 μm.
[0051] The positive electrode active material is a known positive electrode active material used in secondary batteries, and can be a material that can supply lithium to the negative electrode side during charging. For example, lithium cobalt oxide, lithium nickel oxide, and LiNi oxide can be used as positive electrode active materials. 1 / 3 Co 1 / 3 Mn 1 / Various lithium-containing oxides, such as 3O2, lithium manganese oxide, and spinel-based lithium compounds, can be used. Materials that do not supply lithium to the negative electrode side during charging, such as sulfur, oxygen, and lithium sulfide, can also be used. High-nickel ternary cathode materials, such as LiNi6Co2Mn2O2, or even high-nickel ternary cathode materials with a nickel-cobalt-manganese ratio of 8:1:1, can also be used. A single cathode active material can be used, or two or more can be used in combination. The cathode active material can be granular, and its size is not particularly limited. The particles of the cathode active material can be solid particles, hollow particles, or particles with voids. The particles of the cathode active material can be primary particles or secondary particles formed by the aggregation of multiple primary particles. The average particle size (D50) of the cathode active material ranges from 1 nm to 30 μm.
[0052] 2. Current collector
[0053] The current collector can be made of metal foil or metal mesh, and can be composed of multiple layers of metal foil. Examples of metals constituting the current collector include Cu, Ni, Cr, Au, Pt, Ag, Al, Fe, Ti, Zn, Co, and stainless steel. The current collector may have a coating on its surface. Furthermore, when the current collector is composed of multiple layers of metal foil, the positive electrode current collector may have an intermediate layer between these layers. The thickness of the current collector is not particularly limited; for example, it can be 0.1 μm or more, 1 μm or more, 1 mm or less, or 100 μm or less.
[0054] 3. Lithium-carbon composite material layer
[0055] The lithium-carbon composite layer contains metallic lithium, carbon materials, and metal nanowires. The term "metallic lithium" encompasses not only elemental lithium but also lithium alloys. Examples include Li-Au, Li-Mg, Li-Sn, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, and Li-Te. The lithium alloy can be of one type or more. With "metallic lithium" at 100% by mass, the mass percentage of the lithium alloy can be adjusted according to the electrode design performance. The mass percentage of the lithium alloy can be above 1%, above 5%, above 10%, or below 40%, below 50%, or below 60%. Carbon materials include anchored carbon materials and non-anchored carbon materials (which can be converted into mobile carbon materials). Anchored carbon materials serve as the fixing and supporting backbone and have through-pores, such as single-walled carbon nanotubes, multi-walled carbon nanotubes, and ordered mesoporous carbon. Mobile carbon materials act as interface modifiers and can move along with the surface of metallic lithium in the negative electrode. Examples of mobile carbon materials include carbon black, graphite, mesophase carbon microspheres, and graphene. With a lithium-carbon composite material content of 100% by mass, the mass percentage of carbon materials can be adjusted appropriately according to the design performance of the lithium-carbon composite material, ranging from 5% to 20%, or even below 65%, 55%, or 45%. There are no special requirements for the combination of anchored and non-anchored carbon materials; anchored carbon materials can encapsulate non-anchored carbon materials, or non-anchored carbon materials can be dispersed and not form a fixed combination with anchored carbon materials. Metal nanowires act as nucleating agents, externally encapsulating anchored carbon materials. Based on material performance requirements, metal nanowires are primarily silver nanowires and copper nanowires, but can also be extended to other types of metal nanowires, such as tin nanowires and magnesium nanowires. Metal nanowires can be used alone or in combination with two or more types. In a lithium-carbon composite material of 100% by mass, the mass percentage of metal nanowires can be above 1%, above 5%, below 25%, below 15%, or below 10%.
[0056] There are no special requirements for the thickness of the lithium-carbon composite material layer; it can be 1 μm or more, 10 μm or more, or 20 μm or more. The thickness of the positive electrode active material layer can be less than 1 mm, less than 500 μm, or less than 100 μm.
[0057] 4. Solid electrolyte
[0058] Solid electrolytes are preferably sulfide-containing solid electrolytes. This is because sulfide solid electrolytes have high ionic conductivity. The sulfide solid electrolyte is Li. 7-x PS 6-x Yx The composition is represented by (Y is at least one of Cl, Br, and I, and x is a number greater than 0 and less than 2). Additionally, solid electrolytes can also be composite solid electrolytes of sulfide solid electrolytes and other solid electrolytes, including lithium lanthanum zirconate, LiPON, and Li... 1+X Al X Ge 2-X (PO4)3, Li-SiO glass, Li-Al-SO glass, and other oxide solid electrolytes are acceptable. There are no special requirements for the thickness of the solid electrolyte layer; it can be 1 μm or more, 10 μm or more, or 20 μm or more. Alternatively, the thickness of the solid electrolyte layer can be less than 1 mm, less than 500 μm, or less than 100 μm.
[0059] 5. Carbon Adaptation Layer
[0060] The carbon adaptation layer comprises anchored carbon material, movable carbon material, and (optionally) alloying elements. In the discharged state, lithium metal is removed through channels such as the vias of the anchored carbon material, the grain boundaries of the movable carbon material, and the contact interface. The remaining anchored carbon material, movable carbon material, and alloying elements constitute the carbon adaptation layer. The anchored carbon material in the carbon adaptation layer is fixed to the metal nanowires, maintaining physical contact between the negative electrode and the solid electrolyte. The movable carbon material moves freely along the lithium metal surface, eliminating hot spots and reducing lithium dendrite formation. The free movement of the movable carbon material is induced by the interfacial pressure. There are no specific requirements for the thickness of the carbon adaptation layer; depending on the electrode design performance requirements, the thickness can be greater than 1 μm, greater than 5 μm, or greater than 10 μm. Alternatively, the thickness can be less than 100 μm, less than 50 μm, less than 30 μm, or less than 15 μm.
[0061] Example 1
[0062] Carbon nanotubes (Shandong Dazhan, GTC-304), carbon black (Hexing Chemical), and lithium carbonate (Aladdin) were uniformly mixed at a mass ratio of 48:48:4. 50 grams of this mixture were then wet-milled with 300 grams of pure water using a ball mill (Tianjin Dongfang Tianjing). After milling, the mixture was placed in a freeze-drying apparatus for drying. The minimum cold trap temperature was -150°C, and the freezing time was 48 hours. The dried mixture was then ablated at 800°C under nitrogen atmosphere. The ablation product is shown below. Figure 3 As shown in the figure, filamentous carbon nanotubes are wound to form a substrate, and granular carbon black is present on the surface. The ablated material is mixed with metallic silver nanowires, metallic lithium and lithium-aluminum alloy in a mass ratio of 30:10:50:10, loaded into a mold, heated to 220℃ to melt, and then extruded to obtain a lithium-carbon composite material.
[0063] The above-mentioned lithium-carbon composite material was rolled to prepare a lithium-carbon composite foil with a thickness of 50 micrometers. The surface electron microscope image of the prepared foil is shown below. Figure 4 As shown in the figure, the spherical carbon nanotube substrate, formed by carbon nanotubes wound around metal nanowires, is bonded to metallic lithium or a lithium alloy. The carbon nanotube spheres anchor the carbon material. Particulate carbon black can also be observed on the surface of the lithium-carbon composite, indicating the movement of the carbon material. To investigate the bonding mechanism between carbon nanotubes and metal nanowires, a small amount of the lithium-carbon composite material was placed in pure water. After the metallic lithium in the composite material reacted completely, the carbon material in the pure water was filtered out, dried, and subjected to electron microscopy. Figure 5 As shown in the figure, it can be clearly seen that carbon nanotubes are wrapped around metal nanowires.
[0064] The above-mentioned 50-micrometer-thick lithium-carbon composite material is rolled onto the blank side of a single-sided positive electrode to prepare a bipolar electrode; or the above-mentioned 50-micrometer-thick lithium-carbon composite material is rolled onto a copper foil, and then a positive electrode slurry is coated on the blank side of the copper foil and dried to prepare a bipolar electrode. The positive electrode material is a ternary positive electrode LiNi6Co2Mn2O2.
[0065] Example 2
[0066] The preparation steps are the same as in Example 1, except that the mass ratio of carbon material to silver nanowires, lithium metal, and lithium-aluminum alloy is changed to 30:10:10:5. The resulting lithium-carbon composite material is as follows: Figure 6 As shown, the spherical anchored carbon materials are scattered and not connected into sheets, making it impossible to prepare a shaped lithium-carbon composite material.
[0067] Comparative Example 1
[0068] Other conditions are the same as in Example 1, except that silver nanowires are not used;
[0069] Comparative Example 2
[0070] Other conditions are the same as in Example 1, except that lithium-aluminum alloy is not used;
[0071] Comparative Example 3
[0072] Other conditions are the same as in Example 1, without the use of silver nanowires and lithium-aluminum alloy;
[0073] Comparative Example 4
[0074] Other conditions are the same as in Example 1, except that carbon black is not used;
[0075] Comparative Example 5
[0076] Standard 50-micron pure lithium strip (Tianjin Zhongneng Lithium Industry Co., Ltd.)
[0077] All-solid-state batteries were assembled using the bipolar electrodes prepared in Example 1 and Comparative Examples 1-5 above, along with a Li4PS3Cl3 sulfide solid electrolyte. Cycle performance tests were performed on the assembled all-solid-state batteries. Figure 7 As shown in the figure, the bipolar electrodes prepared using the materials of Example 1 and Comparative Examples 1-4 have better cycle life than Comparative Example 5. This is mainly due to the role played by the carbon framework in Example 1 and Comparative Examples 1-4. In addition, the synergistic effect of anchored carbon materials and mobile carbon materials greatly improves the interfacial contact, especially when silver nanowires and lithium-aluminum alloys are added (Example 1), the performance of the bipolar electrode is significantly improved. The all-solid-state battery assembled using the materials of Comparative Examples 1-4 has a lower cycle life than Example 1. There are two main reasons for this: first, the lack of metal nanowires and lithium alloys leads to uneven deposition of lithium metal on the negative electrode, making the battery prone to dendrite formation and causing rapid capacity decay; second, the lack of non-anchored carbon material carbon black (Comparative Example 4). Although the carbon nanotube framework can maintain the contact between the negative electrode and other interfaces, the lack of non-anchored carbon material to regulate the lithium metal deposition surface results in a lower cycle life than Example 1.
[0078] It is understood that, although the lithium-carbon particles and their preparation method have been described in detail in conjunction with specific embodiments of the present invention, the above description is merely for the purpose of meeting legal requirements, and the present invention is not limited to the given embodiments. Those skilled in the art can replicate the lithium-carbon powder preparation method based on the disclosure and teachings of the specification through appropriate operations.
[0079] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make appropriate changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the present invention should also fall within the protection scope of the claims of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A bipolar electrode, the bipolar electrode comprising a current collector and a positive electrode active material layer and a negative electrode active material layer respectively located on both sides of the current collector, characterized in that, The negative electrode active material layer includes a lithium-carbon composite material, which comprises metal nanowires, anchored carbon materials, non-anchored carbon materials, and metallic lithium and / or lithium alloys. The anchoring carbon material is a linear carbon material with through holes, the pore size being in the range of 1-100 nm. The linear carbon material is wound around the metal nanowires and interwoven with each other to form a porous support framework. The non-anchored carbon material is at least one material selected from carbon black, graphite, mesophase carbon microspheres and graphene; The non-anchored carbon material and the metallic lithium and / or lithium alloy are distributed in the pores and on the surface of the porous support skeleton.
2. The bipolar electrode according to claim 1, characterized in that, The metal nanowires include at least one of silver nanowires, copper nanowires, tin nanowires, and magnesium nanowires; The linear carbon material with through pores includes at least one of single-walled carbon nanotubes, multi-walled carbon nanotubes, and ordered mesoporous carbon. The lithium alloy includes one or more of Li-Au, Li-Mg, Li-Sn, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, and Li-Te, with the mass percentage of the alloying elements ranging from 1% to 60%.
3. The bipolar electrode according to claim 1, characterized in that, Based on the lithium-carbon composite material as 100% by mass, the mass percentages of metal nanowires, anchored carbon materials, non-anchored carbon materials, and metallic lithium and / or lithium alloys are respectively (1-15):(1-60):(1-60):(35-65).
4. The bipolar electrode according to claim 1, characterized in that, When the lithium-carbon composite material contains both metallic lithium and lithium alloy, the mass ratio of metallic lithium to lithium alloy is (55-95):(5-45).
5. The bipolar electrode according to claim 1, characterized in that, The positive electrode active material layer contains oxide active material or sulfur positive electrode active material; The oxide-containing active materials include rock salt layered active materials, spinel-type active materials, or olivine-type active materials; The sulfur-containing positive electrode active material includes sulfur (S) or lithium sulfide (Li2S).
6. The bipolar electrode according to claim 5, characterized in that, The rock salt layered active substances include LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2; The spinel-type active material includes LiMn2O4 and Li(Ni) 0.5 Mn 1.5 O4, Li4Ti5O 12 ; The olivine-type active substances include LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
7. The bipolar electrode according to claim 5, characterized in that, The positive electrode active material layer contains a high-nickel ternary positive electrode material with a nickel-cobalt-manganese ratio of 3:1:1 to 8:1:
1.
8. An all-solid-state battery, characterized in that, The all-solid-state battery comprises a bipolar electrode according to any one of claims 1 to 7.
9. The all-solid-state battery according to claim 8, characterized in that, During battery discharge, the negative electrode active material layer forms a carbon adaptation layer on its surface facing the solid electrolyte. The carbon adaptation layer has a thickness ranging from 1 micrometer to 15 micrometers and includes a porous support framework and non-anchored carbon material that can move within the carbon adaptation layer.
10. The all-solid-state battery according to claim 9, characterized in that, The carbon-adaptive layer also contains alloying elements.